Cis‐Glyco‐Fused Benzopyran Derivatives as Hit Compounds for the Development of Therapeutic and Diagnostic Tools against Neurodegenerative Diseases. Issue 6 (5th June 2014) - Merlo, Silvia; Sironi, Erika; Colombo, Laura; Cardona, Francisco; Martorana, Alessandra M.; Salmona, Mario; La Ferla, Barbara; Airoldi, Cristina
Abstract Oligomeric and fibrillar aggregates generated by amyloid‐β (Aβ) and prion protein (PrP) peptides are amongst the principal components of amyloid plaques found post mortem in patients suffering from Alzheimer's disease and mammalian prion diseases. Hence these amyloid peptides represent major molecular targets to develop potential drugs and diagnostic tools for the above‐mentioned neurodegenerative diseases. Recently, a small library of cis‐glyco‐fused benzopyran compounds has been synthesized by us, and their ability to recognize and bind Aβ peptide oligomers and stain Aβ deposits was demonstrated. By exploiting the structural similarity between Aβ and PrP aggregates, herein the interaction of these benzopyran molecules with PrP oligomers and their inhibition of the PrP aggregation process that leads to amyloid fibril formation are investigated. Finally, the in vitro staining of PrP fibrils is achieved with a fluorescently labeled cis‐glyco‐fused benzopyran derivative able to cross a model of the blood–brain barrier.